Islam, accounting and finance: challenges and opportunities in the new decade - Mohd. Alwi, Norhayati (IIUM Press, 2011)

(untitled)
There has been increasing evidence that suggests the acceptance of shariah principles for business transactions. Islamic finance products such as Wadiah, Ijarah, Murabahah, Mudarabah, Diminishing Musharakah, Salam, Istisna, Shukuk, just to name a few, have been introduced into the financial market to meet the demand of the financial products that follow the shariah principles. This has important implications on the nature, process and practice of accounting, auditing and governance of financial institutions and organisations.